Cu2AgInS2Se2 quantum dots sensitized porous TiO2 nanofibers as a photoanode for high‐performance quantum dot sensitized solar cell. (4th April 2021) - Kottayi, Roopakala; Murugadoss, Vignesh; Panneerselvam, Pratheep; Sittaramane, Ramadasse; Angaiah, Subramania
Summary: Cu2 AgInS2 Se2 alloyed quantum dots are synthesized through a simple hot injection method. Its tetragonal structure and crystallite size are determined by using X‐ray diffraction analysis. Its optical properties are observed by using Ultraviolet‐Vis absorption and PL emission spectroscopies. The oxidation state and elemental composition of Cu2 AgInS2 Se2 quantum dots are confirmed by X‐ray photoelectron spectroscope analysis and energy dispersive X‐ray analysis, respectively. The optical bandgap of the synthesized quantum dots is measured to be 1.29 eV. The synthesized Cu2 AgInS2 Se2 quantum dots are sensitized onto the porous TiO2 nanofibers (CAISSe/P‐TiO2 ) and its morphological and optical properties are examined. The quantum dot sensitized solar cell is assembled using CAISSe/P‐TiO2, polysulfide and Cu2 S as the photoanode, electrolyte and the counter electrode exhibited photoconversion efficiency (PCE) of 5.87%, which is significantly higher than that assembled using Cu2 AgInSe4 (4.21%) and Cu2 AgInS4 (4.89%) quantum dots sensitized porous TiO2 NFs as the photoanodes. Abstract : Quantum dot sensitized solar cell fabricated with Cu2 AgInS2 Se2 alloy quantum dots sensitized TiO2 nanofibers as photoanode exhibiting higher photoconversion efficiency than that of Cu2 AgInSe4 and Cu2 AgInS4 .